Development of Lignin-Based Terpolyester Film and Its Application to Separator Material for Electric Double-Layer Capacitor. (4th May 2019) - Koda, Keiichi; Taira, Shogo; Kubota, Atsushi; Isozaki, Tomofumi; You, Xiangyu; Uraki, Yasumitsu; Sugimura, Kazuki; Nishio, Yoshiyuki
Abstract : For new application of technical lignins as separator material for electric double-layer capacitor (EDLC), we tried first to prepare bipolyester film by melt-polycondensation of polyethylene glycol lignin (PEGL) and maleic anhydride. The EDLC assembled with this film, however, showed lower electrochemical performance than the reference EDLC with commercial cellulosic separator. Porous bipolyester film was then prepared and the resulting EDLC exhibited improved specific capacitance, but high intrinsic and charge transfer resistances. Non-porous terpolyester film was prepared next, using polyethylene glycol 500, 000 to improve flexibility of the film, which might lower the resistances. This film was flexible enough and provided the resulting EDLC with superior electrochemical performance to the bipolyester film. EDLC with porous terpolyester film was finally prepared and showed the highest electrochemical performance, comparable to the reference EDLC. Porous morphology and flexibility were key factors to fabricate lignin-based self-standing film as separator material for high-performance EDLC.